Defining the kinetics of severe fever with thrombocytopenia syndrome virus acquisition and dissemination in naturally-infected Haemaphysalis longicornis - Esteves, Eliane; Obellianne, Clemence; Garba, Ahmed; Sarkar, Shovon Lal; Schuler, Margaret G.; Hermance, Meghan E. (Frontiers in Cellular and Infection Microbiology, 2025)
Haemaphysalis longicornis is a primary vector of severe fever with thrombocytopenia syndrome virus (SFTSV), an emerging virus of public health concern that can cause severe disease and high mortality rates. For zoonotic tick-borne viruses such as SFTSV, it is critical that specific tick-virus pairings are carefully examined to elucidate the intra-tick infection dynamics that enable viral infection, dissemination, and persistence within a particular tick species. This study investigated the intra-tick kinetics of SFTSV acquisition and dissemination in H. longicornis by feeding nymphs on viremic mice. Nymphs were collected and processed at defined time points during and after feeding, as well as post-molting. Viral RNA was detected in nymph bodies within the first 24 hours of feeding, and infectious virus was subsequently detected at 48 hours. The rates of SFTSV acquisition by H. longicornis nymphs were consistently high across all time points. For infected ticks to be capable of transmitting virus during a subsequent blood meal, the virus must disseminate beyond the tick midgut and ultimately infect the salivary glands. Thus, the kinetics of virus dissemination beyond the midgut and into the hemolymph were evaluated by screening nymph legs for the presence of virus. SFTSV was capable of early dissemination beyond the nymph midgut during blood feeding, as well as at time points after the nymphal blood meal was complete. Furthermore, SFTSV RNA was detected in various tissues of molted adults that had acquired virus as nymphs, and these results demonstrated that time post-molting influences the efficiency and level of virus maintained by transstadial transmission. This is the first study using naturally-infected ticks to demonstrate the kinetics of viral dissemination beyond the midgut for any tick-borne virus. These findings offer new insights into tick-virus interactions that can ultimately guide strategies aimed at disrupting virus maintenance and transmission by ticks.